2017
DOI: 10.17269/cjph.108.5944
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ online discussions about children’s dental caries: A critical content analysis

Abstract: OBJECTIVES: Through an analysis of postings to an online parenting forum, we aimed to explore the many ways in which parents orient to (i.e., take up, challenge, re-articulate) information about child dental health in the context of their online interactions. Our analysis is anchored in Nettleton's theoretical work on dental authority and power, which we apply in a digital context. METHODS:We examined discussion threads from the public online forums on BabyCenter Canada. We identified relevant threads using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…It is a challenge for dental public health to find ways to provide input to the public about the importance of maintaining dental health. Research results in Canada state that changes in the perspective of parents on dental caries in children can be done through online group discussions, especially when they are unable to communicate intensely with the dentist [17].…”
Section: Resultsmentioning
confidence: 99%
“…It is a challenge for dental public health to find ways to provide input to the public about the importance of maintaining dental health. Research results in Canada state that changes in the perspective of parents on dental caries in children can be done through online group discussions, especially when they are unable to communicate intensely with the dentist [17].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have emphasised the utilisation of online parenting forums across all facets of child rearing (Appleton, Fowler, & Brown, ; Milne, Weijs, Haines‐Saah, & McLaren, ; Pedersen & Lupton, ; Ruthven et al, ). Although some researchers have found that the dialogue on these virtual spaces can be contentious (Appleton et al, ), the majority note that they provide a positive means for mothers to express themselves and find the social support they are seeking (Cowie et al, ; Niela‐Vilén et al, ; Pedersen & Lupton, ).…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we study users engaging in discussion threads about vaccination on BabyCenter US, a popular parenting forum. Other studies used this source of data to investigate themes related to vaccination [23] and other topics [24], but none of them performed an analysis at the level of users. Our first contribution consists in detecting users who follow the recommended or alternative vaccination schedule by developing a high-precision classifier that searches relevant comments.…”
Section: Introductionmentioning
confidence: 99%